(untitled) (Journal of Cancer Research Updates, 2024)
This study explores the prospective of risperidone-loaded β-cyclodextrin nanosponges as a therapeutic strategy for managing altered mental status (AMS) and delirium in cancer patients. Almost 87% of patients with advanced cancer experience AMS or delirium, significantly impacting prognosis and quality of life. The present study aims to enhance the solubility, bioavailability, and therapeutic effectiveness of second-generation antipsychotic medication risperidone (RSP), with poor aqueous solubility, it was encapsulated in β-cyclodextrin nanosponges. The nanosponges prepared by fusion technique using different β-CD: DPC molar ratios, were tested for their ability to encapsulation efficiency, drug loading, and dissolutions kinetics. Batch 1, (1:1 molar ratio) exhibits RSP loading capacity (454.2 µg/mg) and encapsulation efficiency (90.84%) along with DSC and FTIR also confirmed that the RSP was successfully encapsulated and without any chemical interactions. In vitro dissolution studies demonstrated a biphasic release profile, with an initial burst followed by sustained release, governed by Fickian diffusion as confirmed by release kinetics modeling. The improved solubility and dissolution profile of the nanosponges will be significant to improve risperidone delivery, ensuring better symptom management in a vulnerable population. These findings highlight the potential of β-cyclodextrin nanosponges as an innovative and adaptable platform for enhancing antipsychotic drug delivery.